The Welfare Costs of Being Off the Grid - Ballon, Paola (World Bank, Washington, DC, 2021)
Digital connectivity has been a critical mitigating factor for the adverse effects of lockdowns implemented in response to the Coronavirus (Covid-19) pandemic on household welfare in Latin America and the Caribbean. Households with access to digital technologies were able to cope better with the shock. rates. More connected households also reported lower income losses, fewer instances of food insecurity and higher access to high quality remote learning. The Coronavirus (Covid-19) pandemic has underlined the importance of ensuring that all segments of the population have access to digital technologies and of promoting digital skills throughout the lifecycle of individuals.